Analysis of the Implementation of Adequate Access to Health Care Based on a Human Rights Perspective: Case Study at Class II A Penitentiary in Padang, Indonesia - Akhirta HB, Desi; Nurcholis, Hanif; Wahyono , Effendi (Manunggal Halim Jaya, 2025)
This research was conducted to analyze the implementation of adequate health access in the Class II A Padang Correctional Institution from a Human Rights (HR) perspective. The study employed a qualitative research method with a descriptive-analytical approach. The results indicate that the provision of health services in the Class II A Padang Correctional Institution has not been guided by HR principles and Human Rights-Based Public Service Standards (P2HAM). Limitations in human resources, inadequate medical facilities and infrastructure, especially for pregnant and breastfeeding women and children, as well as a lack of effective regulations in the application of health standards, are the main factors hindering the fulfillment of health rights for inmates. Furthermore, strengthening regulations and oversight from the authorities is also an essential factor in ensuring that the health rights of inmates can be optimally fulfilled in the Correctional Institution to realize a more humane and just correctional system.